Hops historic photographs of the Oregon hopscape - Helphand, Kenneth I. ca. 20.Jh- (Oregon State University Press, 2020)
"Hops: Historic Photographs of the Oregon Hopscape is a visual dive into the physical presence of a plant that many people discuss but few could identify. Oregon was once the leading producer of hops in the United States (a title now held by Washington). Kenny Helphand has scoured archives across the state to bring together historic photos of hop pickers in the late nineteenth and early twentieth centuries. Hops brings to life pickers of all backgrounds, through different eras of agricultural practice. Here are children, nuns, families, immigrants, and college students in fields, hop driers, and tent camps. The photos range from the candid to the highly professional - including five images from Dorothea Lange's iconic Farm Service Administration work. The 85 high quality photos are accompanied by captions that provide, variously, historical background, selections from oral histories, and visual guidance. A historical essay gives interested readers a short overview of the plant's history and the world of hop growing and picking"--
Keywords: Geschichte; Hopfen -- Art; Hopfenmarkt; Fotografie; Oregon; USA; Hops / Oregon / History; Houblon / Oregon / Histoire; Hops; History